Plasma-assisted “waste-to-energy” processes - Zhovtyansky, V.A.; Kolesnikova, E.P.; Iakymovych, M.V. (Вопросы атомной науки и техники, 2017)
The environmental safety and energy efficiency of the processes of alternative gaseous fuels production based on the conversion of biomass waste using plasma-steam technology are discussed. The plasma-steam installation for waste processing, that eliminates the risk of dioxins and furans production in the process of gasification is briefly described. The problems of minimization nitrogen oxides emission as well as exception into the environment of heavy metals are discussed. It is shown that the proposed variant of the processing technology correspond to the general idea of numerous publications in the world scientific literature, known as the Waste to Energy.